Creative school climate - Vejian, Gajathiswari; Kamarudin, Nurzatulshima; Abdul Kadir, Suhaida (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Creativity can be nurtured and enhanced through education. In schools, creativity is seen as an important force for shaping the development of creativity in the management of schools and in the teaching and learning process. School creative climate is one of the important social factors in influencing motivation, attitudes, behaviors and beliefs of a teacher in their jobs every day. This concept paper discussed the concept of school climate and creative school climate that includes creative organizational climate theory relevant to creativity. The applications of creative school climate for foster creativity are also discussed through literature reviews.